2008
DOI: 10.1175/2007jcli1600.1
|View full text |Cite
|
Sign up to set email alerts
|

The Drought of Amazonia in 2005

Abstract: In 2005, large sections of southwestern Amazonia experienced one of the most intense droughts of the last hundred years. The drought severely affected human population along the main channel of the Amazon River and its western and southwestern tributaries, the Solimões (also known as the Amazon River in the other Amazon countries) and the Madeira Rivers, respectively. The river levels fell to historic low levels and navigation along these rivers had to be suspended. The drought did not affect central or easter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

30
556
0
62

Year Published

2009
2009
2014
2014

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 670 publications
(648 citation statements)
references
References 30 publications
(32 reference statements)
30
556
0
62
Order By: Relevance
“…Likewise, anomalously warm conditions in the southern tropical Atlantic tend to delay the northward migration of the ITCZ and generate wetter-than-normal conditions in the northern Nordeste. These precipitation anomalies can occur on a variety of timescales including intra-annual (e.g., Marengo et al, 2008 andLewis, et al, 2010), decadal (e.g., Hastenrath andHeller, 1977 andShukla, 1996), and, perhaps, centennial/millennial (e.g., Cruz et al, 2009 and this paper). Thus, we posit that the centennial-millennial detrital-rich intervals represented by the Ti/Ca peaks were produced by centennial-millennial increases of regional rainfall that coincided with a cooler northern tropical Atlantic, warmer southern tropical Atlantic, and an anomalously southward-displaced mean position of the ITCZ.…”
Section: Periods Of Anomalous Warmth In the Northern Tropical Atlantimentioning
confidence: 76%
“…Likewise, anomalously warm conditions in the southern tropical Atlantic tend to delay the northward migration of the ITCZ and generate wetter-than-normal conditions in the northern Nordeste. These precipitation anomalies can occur on a variety of timescales including intra-annual (e.g., Marengo et al, 2008 andLewis, et al, 2010), decadal (e.g., Hastenrath andHeller, 1977 andShukla, 1996), and, perhaps, centennial/millennial (e.g., Cruz et al, 2009 and this paper). Thus, we posit that the centennial-millennial detrital-rich intervals represented by the Ti/Ca peaks were produced by centennial-millennial increases of regional rainfall that coincided with a cooler northern tropical Atlantic, warmer southern tropical Atlantic, and an anomalously southward-displaced mean position of the ITCZ.…”
Section: Periods Of Anomalous Warmth In the Northern Tropical Atlantimentioning
confidence: 76%
“…[11] The elevated mortality observed in the Central Amazon in 2005 is unlikely to be related to the 2005Ama-zon drought since analysis of both rainfall and river discharge data showed that this drought had little effect on Central or Eastern Amazonia [Marengo et al, 2008]. In Manaus, the effects of rainfall anomalies were observed late in the dry season (September-October) [Marengo et al, 2008], whereas the elevated mortality reported here from both Landsat images and forest plot data occurred before the late dry season.…”
Section: Resultsmentioning
confidence: 99%
“…In 2005 the Amazon basin experienced one of the most severe droughts of the past 100 years [Marengo et al, 2008] and analyses of forest plot data suggest that the drought produced elevated tree mortality across the entire Amazon basin [Phillips et al, 2009]. Yet, the 2005 drought most strongly affected western and southwestern Amazonia [Marengo et al, 2008] which raises a question as to whether the tree elevated mortality observed across the basin was the result of drought alone. Here we present an approach linking field-measured tree mortality data, remote sensing analyses, and an empirical model to quantify widespread tree mortality across the Amazon produced by a single squall line observed from January 16 to January 18, 2005.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, in 2009, the Amazon basin was affected by extraordinarily strong rainfalls, which raised the water level of its rivers to a magnitude and duration rarely observed in the region, again causing economic and social damage to the human populations residing there (Marengo et al, 2011a(Marengo et al, , 2012. Extreme climatic events such as these are worrying in the Amazon region not only because they reach riverine populations, but also because they cause a loss of biodiversity (for example, millions of fish died in the 2005 drought in the region).…”
Section: Introductionmentioning
confidence: 99%